Electrostatic stabilization of charged colloidal particles with adsorbed polyelectrolytes of opposite charge - Hierrezuelo, José (Langmuir : the ACS journal of surfaces and colloids, 2010)
Repulsive electrostatic double-layer forces are responsible for the stabilization of charged colloidal particles in the presence of adsorbed polyelectrolytes of opposite and high line charge densities. This mechanism is revealed by studies of electrophoretic mobility and colloidal stability performed with dynamic light scattering as a function of the polyelectrolyte dose and the ionic strength for two different types of latex particles and four different types of polyelectrolytes. The dependence of these quantities is very similar for bare charged latex particles and the same particles in the presence of the different oppositely charged polyelectrolytes. Positively charged particles in the presence of anionic polyelectrolytes behave analogously to negatively charged particles in the presence of cationic polyelectrolytes